Pretreating anaerobic fermentation liquid with calcium addition to improve short chain fatty acids extraction via in situ synthesis of layered double hydroxides. (January 2019) - Sheng, Liang; Liu, Jianyong; Zhang, Cheng; Zou, Lianpei; Li, Yu-You; Xu, Zhi Ping
Graphical abstract: Highlights: Adding calcium was proposed to improve SCFAs extraction from AFL via LDH synthesis. The carbonate removal was up to 76.6% with 0.06 mol/L calcium addition at pH 12. From SCFAs extraction view, the optimal SCFAs/Al 3+ for SCFAs-LDH synthesis is 3.0. Total SCFAs content in SCFAs-LDH with pretreatment was 4.5 times of the control. Abstract: In situ synthesis of layered double hydroxides (LDHs) was proved to be an effective way to extract short chain fatty acids (SCFAs) from anaerobic fermentation liquid (AFL) as carbon source for biodenitrification, but the SCFAs content in SCFAs-LDH was unsatisfactory because of the existence of much carbonate in AFL. Pretreatment of AFL with calcium addition was investigated to remove carbonate and improve SCFAs extraction via LDHs synthesis. Results of batch tests showed that, the carbonate removal efficiency was as high as 76.6% when the calcium addition was 0.06 mol/L at pH 12. When using the optimal SCFAs/Al 3+ ratio of 3.0, the total SCFAs content in SCFAs-LDH with pretreatment was improved to 46.5 mg COD/g LDH, which was 4.5 times of the control (10.4 mg COD/g LDH). These results suggest that adding calcium to AFL was an effective way to eliminate the negative effect of carbonates on SCFAs-LDH synthesis.